Synthesis and Characterization of an Epidermal Growth Factor Receptor‐Selective RuII Polypyridyl–Nanobody Conjugate as a Photosensitizer for Photodynamic Therapy. (22nd October 2019) - Karges, Johannes; Jakubaszek, Marta; Mari, Cristina; Zarschler, Kristof; Goud, Bruno; Stephan, Holger; Gasser, Gilles
Abstract: There is a current surge of interest in the development of novel photosensitizers (PSs) for photodynamic therapy (PDT), as those currently approved are not completely ideal. Among the tested compounds, we have previously investigated the use of Ru II polypyridyl complexes with a [Ru(bipy)2 (dppz)] 2+ and [Ru(phen)2 (dppz)] 2+ scaffold (bipy=2, 2′‐bipyridine; dppz=dipyrido[3, 2‐a:2′, 3′‐ c ]phenazine; phen=1, 10‐phenanthroline). These complexes selectively target DNA. However, because DNA is ubiquitous, it would be of great interest to increase the selectivity of our PDT PSs by linking them to a targeting vector in view of targeted PDT. Herein, we present the synthesis, characterization, and in‐depth photophysical evaluation of a nanobody‐containing Ru II polypyridyl conjugate selective for the epidermal growth factor receptor (EGFR) in view of targeted PDT. Using ICP‐MS and confocal microscopy, we could demonstrate that our conjugate has high selectivity for the EGFR receptor, which is a crucial oncological target because it is overexpressed and/or deregulated in a variety of solid tumors. However, in contrast to expectations, this conjugate was found to not produce reactive oxygen species (ROS) in cancer cells and is therefore not phototoxic. Abstract : Specificity comes to light : Ru II polypyridyl complexes used in photodynamic therapy (PDT) can target DNA. However, because DNA is ubiquitous, the selectivity of such photosensitizers could be increased by linking them to a targeting vector. Herein we present the synthesis, characterization, and in‐depth photophysical evaluation of a nanobody‐containing Ru II polypyridyl conjugate selective for the epidermal growth factor receptor (EGFR) in view of targeted PDT.